Influence of Conflict Management and Work Motivation on Nurse Performance - Joseph Christian Tjahjadi; Kartika Imasari Tjiptodjojo (Jurnal Informatika Ekonomi Bisnis, 2026)
Nurse's work performance is one of the important indicators in assessing the quality and service standard in hospitals and clinics. Various studies state that conflict management and work motivation are factors that influence nurse's work performance in healthcare. This study aims to determine the effect of conflict management and work motivation on nurse's work performance at Clinic X, Bandung. This explanatory research uses a quantitative approach. The population and sample size consist of 34 nurses, taken using total sampling methods. Data was processed statistically using IBM SPSS application, which includes validity, reliability, normality, and heteroscedasticity tests. Hypothesis test was conducted using simple linear regression analysis. The results showed that conflict management did not have a significant effect on nurse's work performance. Work motivation, however, has a significant effect on nurse's work performance.